2016
DOI: 10.1007/s12603-016-0701-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol levels within the high normal range are associated with better cognitive performance among Chinese elderly

Abstract: Objectives-The association between cognitive function and cholesterol levels is poorly understood and inconsistent results exist among the elderly. The purpose of this study is to investigate the association of cholesterol level with cognitive performance among Chinese elderly.Design-A cross-sectional study was implemented in 2012 and data were analyzed using generalized additive models, linear regression models and logistic regression models. Conflict of interestThe authors declare that there are no conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 57 publications
10
43
0
Order By: Relevance
“…On the other hand, dyslipidemia was found to be a protective factor in the present study, which means that the participants who were diagnosed with dyslipidemia had a decreased risk of cognitive decline after stroke. This finding is similar to those of other large studies of older people that reported an association of high triglyceride [44]and LDL levels with better cognitive performance [45].In contrast, a longitudinal study of 1,159 elderly Chinese individuals found associations between the elevated levels of total cholesterol and LDL-accelerated cognitive decline [46]. To elucidate current findings, it may be explained that statin use was associated with a reduced risk of dementia in participants without MCI at the baseline [47].The pleiotropic effects of statin might favorably affect cognitive function through pro-endothelial activity, stabilization of atherosclerotic plaques, antiinflammation, and inhibition of thrombogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, dyslipidemia was found to be a protective factor in the present study, which means that the participants who were diagnosed with dyslipidemia had a decreased risk of cognitive decline after stroke. This finding is similar to those of other large studies of older people that reported an association of high triglyceride [44]and LDL levels with better cognitive performance [45].In contrast, a longitudinal study of 1,159 elderly Chinese individuals found associations between the elevated levels of total cholesterol and LDL-accelerated cognitive decline [46]. To elucidate current findings, it may be explained that statin use was associated with a reduced risk of dementia in participants without MCI at the baseline [47].The pleiotropic effects of statin might favorably affect cognitive function through pro-endothelial activity, stabilization of atherosclerotic plaques, antiinflammation, and inhibition of thrombogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…31 This study demonstrated that a higher concentration of TG was associated with better functional performance and lower risk of decline in functional performance. Our current findings are consistent with our previous studies 11,32 ; they are also supported by accumulating evidence 33,34 that the association between evaluated TG and cognitive impairment might not hold or even be inverted for the oldest old. Lower TGs were negatively associated with ADL performance in women aged 95 years and older 35 and predicted severe disability and higher all-cause mortality in patients with acute ischemic stroke 36 ; additionally, TG has been shown to be a serological marker of frailty.…”
Section: Association Of Tg With Functional Performancesupporting
confidence: 93%
“…There is no exploring the directly relationship between serum lipids and cognitive function in different BMI levels. Yuebin Lv, et al (15) found that TG was associated with MMSE score, but after adjustment for central obesity and other confounding factors, it was not associated with the risk of cognitive impairment. Of the similar studies which have examined whole samples without BMI strati cation, some cross-sectional and prospective studies found inconsistent associations with serum TG ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that lower TG was associated with higher cognitive scores in most cognitive domains (13) and better short-term memory (14). Yuebin Lv, et al (15) found that TG was associated with Mini Mental Status Examination (MMSE) score, but after adjustment for central obesity and other confounding factors, it was not associated with the risk of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%